Alkalizing potential and calcium release of residues from intracanal dressing containing calcium hydroxide - Crespo, Mariana Pires; Pereira, Kamila De Figueiredo; Kuga, Milton Carlos; Porto, Thiago Soares; Armada, Luciana (Universidade Estadual Paulista Júlio de Mesquita Filho, 2018)
AbstractIntroductionIf the restoration, that seal the root canal from oral environment, failed or solubilize, the intracanal dressing could be partially removed, decreasing the efficiency of calcium hydroxide (CH).ObjectiveTo evaluate the alkalizing potential and calcium ions release of intracanal residues from different medications, in different periods.Materials and methodHuman incisors were endodontically instrumented and randomly divided (n=10). The root canals were filled with: G1⎯Calcium hydroxide (CH); G2⎯CH with 0.4% chlorhexidine digluconate (CHC); G3⎯CH with camphorated paramonochlorophenol and glycerin (HPG); G4⎯CH was maintained during all experiment, as positive control group (PC) and G5⎯ No medication was performed in the negative control group (NC). The specimens were immersed in distilled water for 7 days. The intracanal dressing was removed from the experimental groups using F1 instrument (Protaper). The teeth were stored in distilled water for 24 hours, 7, 14 and 28 days. pH value and calcium ions released were evaluated and the data were submitted to ANOVA one-way and Tukey tests.ResultAll experimental groups presented lower alkalizing potential and calcium ions release than PC (P<0.05). No significant difference was found among the experimental groups, regardless of the period (P>0.05).ConclusionThe alkalizing potential and calcium ions release of residues from different intracanal dressing, in different periods, were similar and lower than the positive control group, that the medication was maintained inside the root canal, encouraging the replacement of intracanal dressing when the restoration fail.

ResumoIntroduçãoSe a restauração temporária, que sela o canal radicular contra o meio bucal, falhar ou solubilizar, a medicação intracanal pode ser parcialmente removida, diminuindo a eficiência do hidróxido de cálcio (CH).ObjetivoAvaliar o potencial alcalinizante e a liberação de íons cálcio de resíduos de diferentes medicações intracanal, em diferentes períodos.Material e métodoIncisivos humanos foram endodonticamente instrumentados e divididos aleatoriamente (n=10). Os canais radiculares foram preenchidos com: G1⎯Hidróxido de cálcio (CH); G2⎯CH com 0.4% de digluconato de clorexidina (CHC); G3⎯CH com paramonoclorofenol camforado e glicerina (HPG); G4⎯CH mantido durante todo experimento, como controle positivo (PC) e G5⎯Sem medicação intracanal, como controle negativo (NC). Os espécimes foram imersos em água destilada durante 7 dias. A medicação intracanal foi removida dos grupos experimentais com um instrumento F1 (Protaper). Os dentes foram armazenados em água destilada por 24 horas, 7, 14 e 28 dias. Os dados foram submetidos aos testes ANOVA one-way e Tukey.ResultadoTodos os grupos experimentais tiveram redução no potencial alcalinizante e na liberação dos íons cálcio, quando comparados ao controle positivo (p<0.05). Não houve diferença estatisticamente significante entre os grupos experimentais, independente do período (p>0.05).ConclusãoO potencial alcalinizante e a liberação de íons cálcio dos resíduos de diferentes medicações intracanal, em diferentes períodos, foram similares entre si e menores que o controle positivo, onde a medicação foi mantida dentro do canal radicular, encorajando a sua troca quando a restauração falhar.
Potencial de alcalinização e liberação de cálcio de resíduos de medicação intracanal contendo hidróxido de cálcio
Keywords: Intracanal dressing; calcium hydroxide; chlorhexidine; endodontics; Curativos biológicos; hidróxido de cálcio; clorexidina; endodontia